The Value of Freedom as a Worldview Factor of Psychological Well-Being - Gruzinova, Ksenia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article is devoted to researching the connections between the values of freedom and life wisdom with psychological well-being. The survey had conducted in the form of a written group survey of respondents. In the research, the following research methods were provided: questionnaire "Value Orientations" by M. Rokych; methods of diagnosing the subjective well-being by R.M. Shamionov, TV Beskova; K. Riff's psychological well-being scale. The results of the research were analyzed by using statistical processing methods.The relationship between the values of freedom and life wisdom with the components and aspects of psychological well-being has been identified. It is determined that the value of freedom is positively correlated with the general level of psychological well-being and contributes to the experience of happiness through the realization of the autonomy, ability to build relevant and meaningful goals in life and a sense of personal growth. The dominance of the value of life wisdom is related to the level of psychological well-being and its components in a negative way. It has been stated that the orientation towards the value of freedom is inversely related to hedonistic well-being, and the dominance of this value does not contribute to the feeling of happiness. On the basis of the conducted research the perspective directions of work directed on preservation of optimum psychological well-being in the conditions of remote activity and recreation have been defined. These areas of work include learning the ability to find a balance between activities and recreation and learning effective forms of recreation through online resources.The role of values of freedom and life wisdom as a worldview factor of well-being was proved, the peculiarities of their interdependence during the pandemic were studied.
Keywords: worldview; components of psychological well-being; aspects of well-being; pandemic; value of freedom; life wisdom